Improving nitrogen fertilizer efficiency with the addition of compost extracts to kailan (Brassica oleracea L.) plants with wick hydroponic cultivation - Tri Fitriani; Darwin Habinsaran Pangaribuan; Ainin Niswati; Sri Yusnaini (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
The goal of this research was to observe the impact of the application of the forms of compost extract and urea fertilizer on the development of kailan plants in the hydroponic wick method. The experiment consisted of was arranged in a completely randomized factorial design with the first element reflecting the compost type: no compost extract, cow manure compost extract, rice straw compost extract, and vermicompost extract. The second element was the use of 0, 100 and 200 kg ha-1 nitrogen fertilizers. The usage of vermicompost extract shows the maximum growth (59.27 cm), amount of leaves (23.00), overall plant weight (93.92 g plant-1), canopy weight (61.37 g plant-1), dried foliage weight (7.17 g plant-1), fresh root weight (33.40 g plant-1), leaf greenness (183.80 SPAD) and nutrient uptake (6.32 g plant-1). The optimal nitrogen fertilizer application was found to be 200 kg ha-1, which culminated in the maximum plant height (42.18 cm), number of leaves (17.75), overall plant weight (60.42 g plant-1), leaf greenness (166.23 SPAD) and N uptake (3.73 g plant-1). With the addition of 100 kg of urea ha-1, vermicompost extract achieved the maximum N absorption efficiency of 112.05 per cent. The use of vermicompost extract in the production of crops with a hydroponic wick method could fulfill the nutrient requirements of plants.